Housing of Animals : Construction and Equipment of Animal Houses. - Maton, A. (Developments in agricultural engineering., 1985)
Animal husbandry plays an increasingly important role throughout the world in the fulfillment of the primary need of mankind: food. The growing demand for food leads to an intensification of the production of livestock and because of the varying climatic conditions in many parts of the world, livestock has to be housed in suitable accommodation during certain times of the year. This book brings together a descriptive as well as a scientific study of all aspects of the housing of all animals; construction of and building materials to be used for the houses and facilities; work organisat.